Intelligent tutoring system for web-based education - Zakaria, Azizi; Siraj, Fadzilah (2000)
Intelligent Tutoring System (ITS) is a branch of Artificial Intelligence (AI) that attempts to simulate a "human like" tutoring capabilities.The term "intelligent" refers to a system with the ability to know what to teach, when to teach and how to teach.Such a tutoring system can be effective because it can respond to the specific needs of student, guide slow learners, challenge rapid learners and monitor the progress of each student as well as establishing a training plan.ITS have the ability to understand, learn, and solve problems just like the human counterpart.To date education trend is geering towards Web-based education.However, Web-based education is still in the early development stage and most of the base education.However, Web-based education is still in the early development stage and most of the courses offered does not contain intelligent capability in real sense.This paper discusses the state of the art of Web-based Intelligent Tutoring System and suggests way to enhance the current Web-based ITSs.